2016
DOI: 10.1093/jxb/erw020
|View full text |Cite
|
Sign up to set email alerts
|

A partial loss-of-function mutation in an Arabidopsis RNA polymerase III subunit leads to pleiotropic defects

Abstract: HighlightAnalysis of the first known viable RNA polymerase III subunit mutant in Arabidopsis reveals novel roles for this complex in maintaining RNA homeostasis, adjusting the expression of a diverse suite of genes, and indirectly modulating alternative splicing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The subtle phenotypes associated with the muse7 single mutants suggest that MUSE7 does not play a dramatic general role in immunity. Similar observations were made for several other muse mutants (Johnson et al ., , ). The increased level of SNC1 protein in muse7‐2 snc1 relative to snc1 did not correlate with elevated SNC1 transcription (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subtle phenotypes associated with the muse7 single mutants suggest that MUSE7 does not play a dramatic general role in immunity. Similar observations were made for several other muse mutants (Johnson et al ., , ). The increased level of SNC1 protein in muse7‐2 snc1 relative to snc1 did not correlate with elevated SNC1 transcription (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 published MUSE proteins, seven have been shown to play essential roles in NLR protein turnover (Huang et al ., ,b, ; Xu et al ., ; Copeland et al ., ). The other three include MUSE4/NRPC7, an RNA polymerase III subunit for which a partial loss‐of‐function mutation results in pleiotropic defects (Johnson et al ., ); MUSE5/AtPAM16, a component of the protein import motor in the mitochondrial inner membrane that negatively affects ROS production and immunity (Huang et al ., ); and MUSE9/SPLAYED, a SWI/SNF chromatin remodeler that affects SNC1 gene expression (Johnson et al ., ). Together, these reports demonstrate the efficacy of the MUSE screen in identifying new components that are involved in plant immunity.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the normal functioning of the subunit is altogether critical for plant development and survival. Recently, Johnson et al 60. demonstrated that a loss-of-function mutant of Arabidopsis RNAPIII subunit nrpc7-1 displayed multiple phenotypic defects including dwarf morphology, stunted siliques and serrated leaves60.…”
Section: Discussionmentioning
confidence: 99%
“…In zebra fish, a mutation resulting from a premature stop codon at Rpc9 locus impairs hematopoietic stem and progenitor cell maintenance (Wei et al, 2016). The nrpc7 mutation occurs in a gene encoding the Arabidopsis thaliana ortholog of the yeast RNAPIII subunit RPC25, which causes altered expression of a number of RNA molecules and a pleiotropic development abnormality in plant morphogenesis (Johnson et al, 2016). Meanwhile, several reports have demonstrated that the fine modulation of RNAPIII transcription mediated by key factors is also essential for normal organism development.…”
Section: Fl3 As a New Regulator In Rnapiii Transcription Machinerymentioning
confidence: 99%